Melatonin Attenuates Contrast-Induced Nephropathy in Diabetic Rats: The Role of Interleukin-33 and Oxidative Stress - Didem Onk; Oruc Alper Onk; Kultigin Turkmen; Huseyin Serkan Erol; Tulin Akarsu Ayazoglu; Osman Nuri Keles; Mesut Halici; Ergun Topal (Hindawi Limited, 2016)
Background. Inflammation and oxidative stress (OxS) contribute to the pathogenesis of diabetic kidney disease (DKD) and contrast-induced nephropathy (CIN). Patients with DKD were found to be more prone to CIN. Interleukin-33 (IL-33) is a proinflammatory cytokine, but its role in DKD and CIN is unknown. Methods. Thirty male Sprague-Dawley rats were enrolled. The first group was comprised of healthy rats (HRs), whereas the other four groups were made up of diabetic rats (DRs), diabetic rats with contrast-induced nephropathy (CIN + DRs), melatonin-treated diabetic rats (MTDRs), and melatonin-treated CIN + DRs (MTCIN + DRs). All groups except the HRs received 50 mg/kg/day streptozotocin (STZ). CIN + DRs were constituted by administrating 1.5 mg/kg of intravenous radiocontrast dye on the 35th day. MTDRs and MTCIN + DRs were given 20 mg/kg/day of intraperitoneal injection of melatonin (MT) from the 28th day for the constitutive seven days. Results. We observed increased IL-33 in the kidney tissue following induction of CIN in DRs. To determine whether MT is effective in preventing CIN, we administered MT in CIN + DRs and demonstrated that kidney tissue levels of OxS markers, inflammatory cytokines, and IL-33 were significantly diminished in MTCIN + DRs compared with other groups without MT treatment (p<0.05). Conclusion. Inhibition of IL-33 with MT provides therapeutic potential in DKD with CIN.